Scanning Electron Microscopic Study of External Morphology and sense organ of cigarette beetle ‘Lasioderma serricorne’ - S. M. Pidhekar; M. O. Wankhade; G. B. Kale; R. M. Chavan; N. B. Kutemate (The Bioscan, 2024)
Insect Sensillia play important role in chemical signaling mating location and reproductive behavior in different type of beetles. Antennae extend from the head and play a crucial role in detecting chemical cues, temperature changes, and other sensory information. Scanning Electron microscopic study is important for the study of how numerous sensillia are present on antenna, mouth and legs part of beetle, generally, five type of sensitive unit(mechanoreceptor) set up on substantially on beetle’s body. Trichoid sensilla They likely play a role in detecting volatile compounds, such as pheromones or environmental odors. long hairs 1- 3 unbranched dendrites covered by a thick cuticle. Basiconic sensilla are responsible for the odor’s perception. shorter with 1- 3 fanned dendrites and a thicker cuticle. All member of flagellum has a narrow base ranging from 19 to 23 μmperiphery only Bristle type sensilla mechanical stimuli generated by the external environment, making them exteroceptors. Bristle sensilla are also found at the base of chemosensory sensilla. Basiconicum and styloconicum are having olfactory function. Coeloconic sensilla are specialized chemosensory structures found on the antennae of beetles. They are abundant and are primarily located on the flagellum (the segmented part of the antenna). we also attempted to discuss the functions of all sensilla.